Persistent and recurrent Trichomonas vaginalis infections: epidemiology, treatment and management considerations. Issue 6 (June 2014) - Seña, Arlene C; Bachmann, Laura H; Hobbs, Marcia M
<x xml:space="preserve">Abstract</x> Trichomonas vaginalis (TV) is a common sexually transmitted infection that can cause vaginitis, cervicitis and urethritis. Persistent and recurrent TV infections are frequent in women, potentially due to the lack of routine screening recommendations for this pathogen, the chronic nature of some infections, and drug resistance. Metronidazole and tinidazole are two oral drugs that are effective against trichomoniasis. There are few alternative treatment options for persons with a metronidazole allergy or treatment failure. Most TV isolates from women with treatment failures that have been analyzed for susceptibility testing in the United States have exhibited low-level metronidazole resistance, supporting the initial use of tinidazole for patients who fail metronidazole therapy. Several non-nitroimidazole drugs and other agents have demonstrated acceptable in vitro activity or cure rates in case reports for metronidazole-resistant trichomoniasis; however, clinical trials are imperative to evaluate their efficacy as alternative therapeutic regimens for this highly prevalent infection.